Current developments in peritoneal glucose transport and sodium-glucose co-transporter 2 inhibitors during peritoneal dialysis - Fan Yang; Cong-hui Liu; Xiao-qi Wang; Xiao-jing Liu; Ya-nan Shi; Zhong-xin Li (Editorial Department of Journal of Clinical Nephrology, 2023)
As a novel widely used drug, sodium-glucose co-transporter (SGLT) 2 inhibitor may lower blood glucose in type 2 diabetics through blocking SGLT2 to curtain glucose reabsorption in proximal renal tubular cells. At the same time, this drug may bring significant renal and cardiovascular benefits to both diabetics and non-diabetics. Human peritoneal mesothelial cells (HPMCs) from peritoneal dialysis (PD) patients can express SGLT. Studies of SGLT2 inhibitors in PD have been reported in in vitro or animal experiments. Using SGLT2 inhibitors in PD patients can reduce peritoneal glucose absorption and delay the progress of peritoneal fibrosis. At the same time, prolonged use of peritoneum and maintenance of transport function are conducive to ensuring dialysis adequacy and optimizing the prognosis. However, application of SGLT2 inhibitors during PD has not attracted extensive attention. This review focused upon the developments of peritoneal glucose metabolism and SGLT2 inhibitors during PD.